Faktor–Faktor Yang Memengaruhi Produksi Usaha Budidaya Ikan Lele Di Kabupaten Bogor (Forum Agribisnis, 2026)
Catfish farming is a significant aquaculture subsector that substantially contributes to food security and the regional economy, including Bogor Regency, which has been designated as a catfish development center in West Java. This study aimed to analyze the production factors influencing the output of catfish farming in Bogor Regency. The research utilized cross-sectional data collected from 82 catfish farmers selected through purposive sampling. Data were analyzed using multiple linear regression with the Cobb-Douglas production function, employing input variables such as pond area, seed, feed, labor, and other production inputs. The results showed that pond area, seed, and feed had a significant positive effect on production, indicating that these inputs are the primary determinants that enhance rearing capacity, stocking density, and fish growth. Conversely, labor and other inputs had a negative and significant effect. It suggests inefficient labor allocation and inappropriate application procedures for other inputs. The coefficient of determination of 79.4 percent indicates that the model can explain production variations substantially. These findings suggest that increasing catfish farming production in Bogor Regency can be achieved through optimizing the use of pond size, seed, and feed, as well as improving labor efficiency and standardizing the use of other inputs to enhance productivity and overall farm efficiency.